Analysis of Website Service Quality of Sistem Perizinan Online Kota Tasikmalaya (SIPENTAS) Using the Modified Webqual 4.0 and Importance Performance Analysis (IPA) Methods - Rosita, Dea; Shofa, Rahmi Nur; Sulastri, Heni (Deparment Information System, Siliwangi University, 2025)
Sistem Perizinan Online Kota Tasikmalaya (SIPENTAS) is a web-based service used to simplify the public licensing process. The existence of SIPENTAS is expected to increase the efficiency and effectiveness of services and support the implementation of online-based government in Tasikmalaya City. However, until now there has been no evaluation of the quality of the website based on user perceptions so it is not known to what extent this system meets user expectations and needs. This study aims to analyze the quality of the SIPENTAS website using Modified Webqual 4.0 which consists of four dimensions: Usability Quality, Information Quality, Interaction Quality, and Interface Quality and uses the Importance Performance Analysis (IPA) method to compare the level of performance and user interests and determine improvement priorities through quadrant mapping. The results of the study indicate that the quality of SIPENTAS is in the good category, with an average value of the level of conformity between performance and user expectations obtaining a percentage of 87.35%, an average value of the gap level of -0.58, and the results of the quadrant analysis there are six indicators that are priority for improvement related to the dimensions of Usability Quality and Interface Quality. Therefore, even though the quality of SIPENTAS services is in the good category, improvements to the six indicators need to be made so that website performance is more optimal and meets user expectations.